Determinants of The Islamic Social Reporting Disclosure - Sunarsih, Uun; Ferdiansyah, Ferdiyansyah (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2017)
The issue of corporate responsibility was a warm up for discussion. This study aimed to analyze the influence of company issuing sukuk, size, and profitability on the disclosure of Islamic Social Reporting. This study uses secondary data obtained through the site www.bapepam.go.id and www.idx.co.id by using purposive sampling. The results showed that only size that affect the disclosure of ISR, so the larger the total assets of the greater disclosure of Islamic Social Reporting. Sukuk issuance has no effect because the ownership structure of companies in Asia, including Indonesia tends to family ownership concentration. Profitability has no effect because the company has a perspective that is different to the Islamic Social Reporting.DOI: 10.15408/aiq.v9i1.3771